ANALYTICAL MODELING OF INORGANIC CONTAMINANTS IN LEACHATE - GONULLU, MT (SAGE PUBLICATIONS LTD, 1994)
The need for estimating the contaminant concentration of leachates from landfills has rapidly become important because of the increased demand for landfilling, causing serious pollution of water bodies in some places. The present study examines the movement of inorganics from waste into leachate in the course of time. Inorganics are discussed in two groups according to their solubilities in water. The first group of inorganics dissolve immediately in water (i.e. at time t = 0). The inorganic compounds of the second group transfer into water over a longer period of time. The mathematical model is based on a porous and well-mixed medium, and on assumptions of dissolution/dilution and mass transfer according to their infiltration rate. The agreement between theoretical and experimental results from laboratory and literature are investigated. After experimental verification, some mathematical relationships to predict the mass transfer coefficient (k) and maximum concentration (C(max)) were also investigated.
Keywords: LANDFILLS; LEACHATE; MATHEMATICAL MODELING; INORGANICS; CHLORIDE; SODIUM; POTASSIUM; TOTAL SOLIDS; SEASONAL WASTES; Engineering; Environmental Sciences & Ecology